“How do we get to them?” Insights on Preconception and Interconception Health for Women in Rural Northwest Ohio - Akia D. Clark; Natalie A. DiPietro Mager (Ohio Journal of Public Health, 2022)
Background: Rural women in the United States are at increased risk for poor preconception and interconception health. In a previous study, women living in Hardin County, a Primary Care Health Professional Shortage Area and maternity care desert in rural northwest Ohio expressed their concerns and their need for more resources to improve their health. As a follow-up study, key informants of Hardin County were interviewed to provide further insight on current resources for preconception and women’s health available to community members, barriers and challenges community members face, and interventions could be implemented in the county to improve health and pregnancy outcomes. Methods: A purposive sample of 14 key informants from community assets in Hardin County were recruited and individually interviewed with semistructured questions from 2 domains: perceived needs and barriers to care. Interview recordings were transcribed, precoded, and thematically analyzed. Participants received a 20 gift card as a token of appreciation. Results: Three themes were characterized from the data: current resources available, community observations, and suggested intervention strategies. Key informants identified the federally-qualified health center and YMCA, among others, as potentially underutilized resources for reproductive-age women. The small-town culture was described as both an advantage and disadvantage when trying to raise awareness about preconception/interconception health. Interventions built on partnerships and utilizing various outlets were suggested. Childcare, intergenerational knowledge transfer, and trust were issues crossing multiple themes. Conclusion: Key informants gave direction on available resources for reproductive-age women and potential approaches to provide education and outreach regarding preconception/interconception health and care.
Keywords: Preconception care; Women& #x27; s health; Female; Rural population; Qualitative research